2013
DOI: 10.1016/j.engfracmech.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the prediction of fatigue delamination growth in composites and adhesive bonds – A critical review

Abstract: An overview is given of the development of methods for the prediction of fatigue driven delamination growth over the past 40 years. Four categories of methods are identified: stress/strain-based models, fracture mechanics based models, cohesive-zone models, and models using the extended finite element method. It is highlighted that most models are phenomenological, based on the observed macro-scale behaviour of test specimens. It is suggested that a more physics based approach, focusing on elucidating the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
152
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 228 publications
(156 citation statements)
references
References 187 publications
(305 reference statements)
2
152
0
2
Order By: Relevance
“…This phenomenon, i.e. that when plotting da/dN as a function of ∆(K 2 ) tests at low R ratios appear to be more severe than tests at high R ratios, also follows from the crack growth data presented in [67] and, as previously remarked is also seen from plotting delamination growth as a function of ∆G, see [17,18,43]. Therefore, it is best to follow the natural extension of the original Paris hypothesis [22,24] and relate da/dN to ∆√G (or �G max ), rather than to ∆G or G max or alternatively, as first suggested in [61,62] to Δ√W rather than by ΔW.…”
Section: Alternative Fracture Mechanics Based Approachessupporting
confidence: 68%
See 4 more Smart Citations
“…This phenomenon, i.e. that when plotting da/dN as a function of ∆(K 2 ) tests at low R ratios appear to be more severe than tests at high R ratios, also follows from the crack growth data presented in [67] and, as previously remarked is also seen from plotting delamination growth as a function of ∆G, see [17,18,43]. Therefore, it is best to follow the natural extension of the original Paris hypothesis [22,24] and relate da/dN to ∆√G (or �G max ), rather than to ∆G or G max or alternatively, as first suggested in [61,62] to Δ√W rather than by ΔW.…”
Section: Alternative Fracture Mechanics Based Approachessupporting
confidence: 68%
“…Here it should be recalled that, when originally formulating the equations for crack growth, Paris argued that, since Irwin [20,21] had shown that the stress-intensity factor, K, uniquely characterises the near tip stress field, then the rate of FCG should be a function of ΔK and K max [22,23]. In [24] [2,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. (Where ∆√G is given by (�G max -�G min ); and G min is the minimum value of the energy release-rate in a fatigue cycle.…”
Section: Analysis Of the Measured Fcg Datamentioning
confidence: 99%
See 3 more Smart Citations